Structural model of patient-centered communication and diabetes management in early emerging adults at the transfer to adult care. - Baker, Ashley C.; Wiebe, Deborah J.; Kelly, Caitlin S.; Munion, Ascher; Butner, Jonathan E.; Swinyard, Michael T.; Murray, Mary; Berg, Cynthia A. (Journal of Behavioral Medicine, 2019)
Early emerging adulthood (ages 18–25) is a time of risk for type 1 diabetes (T1D) when relationships with parents and providers are changing. We examined whether individuals' high-quality relationships with mothers are associated with greater perceptions of patient-centered communication (PCC) with their doctor and whether PCC is associated with better adherence and glycemic control through diabetes-related self-efficacy. Additionally, we tested whether associations of PCC with self-efficacy and diabetes outcomes are stronger among those who had transferred to adult care. One-year post-high school, 217 individuals with T1D (60% women, 53% in adult care) reported perceptions of maternal relationship quality, PCC, self-efficacy, and adherence. Glycemic control was measured via HbA1c assay kits. Structural equation modeling indicated good model fit and revealed indirect paths linking higher maternal relationship quality to better adherence through higher PCC, and higher PCC to better HbA1c through adherence. Transfer status moderated the link between PCC and self-efficacy, suggesting PCC may be especially important when emerging adults transfer to adult care.